Spin–orbit torque-assisted switching in magnetic insulator thin films with perpendicular magnetic anisotropy - Peng Li; Tao Liu; Houchen Chang; Alan Kalitsov; Wei Zhang; Gyorgy Csaba; Wei Li; Daniel Richardson; August DeMann; Gaurab Rimal; Himadri Dey; J. S. Jiang; et al. (Nature Communications, 2016)
By virtue of strong spin-orbit coupling, a current-carrying heavy metal may generate a torque on the magnetization of an interfaced ferromagnetic metal. Here, the authors demonstrate how this effect assists the magnetic reversal of ferromagnetic insulators with perpendicular magnetic anisotropy.